From carnism to veganism : "once I knew, I didn't want to have any part in it whatsoever" : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University, Albany, Aotearoa New Zealand - Field, Emilie Rita (Massey University, 2020)
Widespread and intensive animal agriculture practices generate extreme suffering and have devastating environmental consequences; thus, veganism is a significant and timely social justice movement. On an individual level, becoming and being vegan can have far-reaching emotional and social consequences. This research aims to explore the experiences of the transition to veganism and of being vegan in a hegemonic meat culture. Assuming a Critical Animal Studies standpoint, personal narrative analysis was used to explore the stories of 12 vegans. Apparent was that the transition to veganism consists of various pathways involving a disruption in some form, critical awareness, engagement in moral reflexivity, and ultimately a determination made on the basis of core beliefs. The characteristic of openness and the personal value of justice appear to be critical in facilitating this process. Once vegan, experiences are generally different to participants’ previous expectations of veganism. They report hoping that the sharing of their practice on an individual level can lead to broader social transformation by offering examples of new ways of living and counter-discourses to the norm of carnism.
Keywords: 520401 Cognition; 300306 Animal welfare